Pendidikan Karakter Gotong Royong melalui Implementasi Kurikulum Merdeka pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SDN 15 Ampang Gadang - Arismanto, Arismanto; Rahman, Yulia (ANWARUL, 2025)
This research was motivated by several problems, namely, the implementation of the Pancasila student profile which was not optimal, especially regarding mutual cooperation. There are still students who have difficulty carrying out learning using collaborative methods at SDN 15 Ampang Gadang. The spirit of cooperation is fading among students at SDN 15 Ampang Gadang. Therefore, this research aims to determine Mutual Cooperation Character Education through the Implementation of the Independent Curriculum in Islamic Religious Education and Character Education Subjects at SDN 15 Ampang Gadang. The method in this research uses descriptive qualitative, namely, to reveal facts, circumstances, phenomena and circumstances that occur while the research is running. The informants in this research were Islamic Religious Education and Character Teachers. Meanwhile, the location of this research was carried out at SDN 15 Ampang Gadang and the data collection techniques used in this research were observation, interviews and documentation. The results of the research obtained regarding Mutual Cooperation Character Education through the Implementation of the Independent Curriculum in Islamic Religious Education Subjects are that Islamic Religious Education teachers appreciate and strongly support Mutual Cooperation Character Education. This form of appreciation was realized by creating a congregational noon prayer program in turns. The implementation of Mutual Cooperation Character Education is carried out at the planning, implementation and evaluation stages. Moral knowing from the planning, implementation and evaluation stages is quite good, because it is in accordance with theory. While the moral feeling is less formed, the moral action is more visible, because there is already a practice of mutual cooperation in implementation. The supporting factors are adequate facilities and infrastructure. The inhibiting factor is the lack of students' understanding of what must be done, in other words the lack of awareness of students to work together.